2003
DOI: 10.1111/1467-9604.00294
|View full text |Cite
|
Sign up to set email alerts
|

Listening to the ‘voices’ of students with severe learning difficulties through a task‐based approach to research and learning in physical education

Abstract: In this article, Hayley Fitzgerald, Anne Jobling and David Kirk consider the physical education and sporting experiences of a group of students with severe learning difficulties. Their study is thought provoking, not only because of the important and somewhat neglected subject matter, but equally for the research approach adopted. The way in which the study engaged with the students and the insights gained from that engagement will be of particular interest to practitioner researchers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 13 publications
1
51
0
1
Order By: Relevance
“…When Peter, Axel and Daniel described how it happened and on whose initiative, it was obvious that the parents were important. The results thereby support the research that has shown that it is most often adults close to the child who express and protect the child's needs (Fitzgerald et al, 2003). Moa's story is, however, an exam-ple of negative discrimination and of how such inadequate treatment and lack of understanding of the child's needs result in crushed self-esteem (Blinde & McCallister, 1998;Goodwin & Watkinson, 2000).…”
Section: Establishing Oneself In Sportsupporting
confidence: 85%
See 2 more Smart Citations
“…When Peter, Axel and Daniel described how it happened and on whose initiative, it was obvious that the parents were important. The results thereby support the research that has shown that it is most often adults close to the child who express and protect the child's needs (Fitzgerald et al, 2003). Moa's story is, however, an exam-ple of negative discrimination and of how such inadequate treatment and lack of understanding of the child's needs result in crushed self-esteem (Blinde & McCallister, 1998;Goodwin & Watkinson, 2000).…”
Section: Establishing Oneself In Sportsupporting
confidence: 85%
“…While some research has examined teachers' experiences of Physical Education and Health (PEH), a gap exists in the literature about the experiences of children and young people with disabilities involved in sport activities (c.f., Fitzgerald, Jobling, & Kirk, 2003;Smith & Thomas, 2006). For many children and young people, sport forms a significant part of their lives, shaping their development into members of society and the sorts of people they become.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some pupils with SEN spend less time in PE lessons and often participate in a narrower PE curriculum when compared to their cohort (Atkinson and Black, 2006;Fitzgerald, 2005;Fitzgerald et al, 2003aFitzgerald et al, , 2003bGoodwin and Watkinson, 2000;Morley et al, 2005;Smith, 2004;Smith and Green, 2004;Sport England, 2001). In attempting to explain these unequal experiences, Smith (2004: 45) suggests that many of the PE teachers that he interviewed claimed to provide 'as much opportunity as possible' in order to meet their legal obligation to include pupils with SEN.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Barton (1993) stressed the need for those involved in teaching physical education to listen to the voices of young people with disabilities and those supressed in and through traditional practices (Garrett, 2006). Whilst some studies offer perspectives of young people with disabilities in physical education (Fitzgerald, 2005;Fitzgerald & Jobling, 2004;Fitzgerald, Jobling, & Kirk, 2003a) 'much research in the field has failed to explore the actual nature of young disabled people's experiences from their viewpoint' (Fitzgerald, Jobling, & Kirk, 2003b, p. 192). Listening to the voices of autistic children requires a degree of creativity and sensitivity (Bishton & Lindsay, 2011) and also consideration of theoretical perspectives that allow their voice and experiences to be accentuated.…”
Section: Introductionmentioning
confidence: 99%